2015
DOI: 10.1002/asjc.1153
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Perturbation Stochastic Approximation with Norm‐Limited Update Vector

Abstract: This paper addresses the convergence of simultaneous perturbation stochastic approximation (SPSA) with a norm‐limited update vector. We first illustrate an unstable solution of the standard SPSA algorithm which motivates the consideration of a modified version, where the norm of the update vector is limited to a certain value. Next, a result on the almost‐sure convergence is presented by reducing the modified algorithm into the standard SPSA algorithm and restricting the probability distribution for the pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…(iv) The detailed proof of fact (ii) is shown here. For the first condition, since 0 <âðkÞ < aðkÞ for all k 2 Z 0þ holds from equation ( 13) and C4, it follows a straightforward proof from Tanaka et al 19 which shows that our first condition of C4 0 holds. Now, we prove the second condition of C4 0 , that is,…”
Section: Modified Broadcast Controllermentioning
confidence: 67%
See 3 more Smart Citations
“…(iv) The detailed proof of fact (ii) is shown here. For the first condition, since 0 <âðkÞ < aðkÞ for all k 2 Z 0þ holds from equation ( 13) and C4, it follows a straightforward proof from Tanaka et al 19 which shows that our first condition of C4 0 holds. Now, we prove the second condition of C4 0 , that is,…”
Section: Modified Broadcast Controllermentioning
confidence: 67%
“…Note that the general guidelines to design the gains aðkÞ and cðkÞ can be found in Sections 7.5.1 and 7.5.2 of Spall. 28 For the value of e, we referred to the example given in Tanaka et al 19 and adjusted this value according to the size of the deterministic movement taken by the robots that the user want, that is, the larger the value of e, the larger the deterministic movement of the robots. Figure 5 shows the snapshots of the initial positions of the robots x i ð0Þði ¼ 1; 2; .…”
Section: Numerical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several researchers have indicated that the computation stability should be improved to apply SPSA for practical applications. 45 An effective approach is to explicitly limit the updating amount of design variable. 45 Therefore, the term a k g ^ k false( θ k false) is saturated as follows: In addition, by restricting Δ k double-struckR p to a Bernoulli distribution, equation (27) can be simply rewritten as follows: This improved version is referred to as SPSA with a norm-limited update vector (NLSPSA).…”
Section: Auto-optimization Scheme For the Backlash And Contact Mode C...mentioning
confidence: 99%